Atomic Thickness Catalysts: Synthesis and Applications. Issue 9 (17th June 2020) - Han, Ali; Zhang, Zedong; Li, Xinyuan; Wang, Dingsheng; Li, Yadong
Abstract: Atomic thickness catalysts (ATCs) have shown huge prospects in energy conversion applications due to the prominent advantages in large specific surface area and high density of exposed surface atoms over their bulk counterparts. The established ATCs, including metals (alloys), layered double hydroxides (LDHs), transition metal dichalcogenides (TMDs), transition metal oxides (TMOs), and carbon‐based materials, have exhibited higher efficiency and better catalytic stability than that of commercial noble metal‐based nanocrystals for energy conversion related reactions. In this review, important progress is exemplified from the aspects of synthetic methods (e.g., bottom‐up and top‐down methods) and energy conversion related reactions, for instance, oxygen reduction reaction (ORR), formic acid oxidation reaction (FAOR), methanol oxidation reaction (MOR), ethanol oxidation reaction (EOR), oxygen evolution reaction (OER), hydrogen evolution reaction (HER), and carbon dioxide (CO2 ) reduction reaction (CRR). Furthermore, a valuable insight into the remaining challenges and potential opportunities for ATCs is provided in the fields of energy conversion applications. Abstract : Unique catalytical properties can be achieved when thinning a material down to atomic thickness, rendering them as promising electrocatalysts for surface related applications. In this review, a wide range of representative materials, including layered and nonlayered atomic thickness catalysts (ATCs) are discussed from the aspects of categories of ATCs, synthetic methods, and their energy conversion related applications.